Upregulated antimicrobial immune response mediated by neutrophils in the development from allergic rhinitis to asthma - Li, Lisha; Zhang, Hao; Wang, Xiujie; Wang, Zixi; Cui, Le; Xu, Yingyang; Guan, Kai (Frontiers in Immunology, 2022)
Background: Allergic rhinitis (AR) and asthma are closely related, and AR is regarded as an important risk factor for the onset of asthma. However, the pathogenesis of the development of asthma from AR is still undefined. Objective: The aim of this study was to investigate the mechanisms underlying the development of asthma from AR by comparing the transcriptome features of patients with AR with and without asthma. Methods: Patients with AR with or without asthma caused by weed pollen who presented to the Allergy Clinic of Peking Union Medical College Hospital were recruited for this study. Peripheral blood samples of all the patients were collected during the weed pollen season (September) when the patients had allergic symptoms and outside the pollen season (November) when the patients had no symptoms. Transcriptomic analysis was conducted, and the differentially expressed genes (DEGs) and enriched immune pathways between the patients with AR with asthma (AR-asthma group) and those without asthma (AR group) were identified. In addition, the expression levels of some pivotal differentially expressed RNAs were quantified using quantitative polymerase chain reaction (PCR). Results: During the weed pollen season, the immune-related Gene Ontology (GO) terms with P values <0.05, enriched by the upregulated genes in the AR-asthma group compared to the AR group included antifungal humoral response, neutrophil-mediated killing of bacterium, antibacterial humoral response, antimicrobial humoral immune response mediated by antimicrobial peptides, and regulation of the T cell receptor signaling pathway. The immune-related GO terms with P values <0.05 enriched by downregulated genes were positive regulation of natural killer cell-mediated cytotoxicity, microglial cell activation, natural killer cell activation, and leukocyte-mediated cytotoxicity. The GO term of antimicrobial humoral immune response mediated by antimicrobial peptides was upregulated both during and outside the pollen season, and the upregulated expression of three DEGs (LTF, PF4, and ELANE) included in this term was verified through quantitative PCR. Conclusions: The activation of the antimicrobial immune response mediated by neutrophils and the depression of cytotoxicity mediated by natural killer cells may play roles in the progression from AR to asthma.